Constraints on the outer radius of the broad emission line region of active galactic nuclei. Issue 1 (5th February 2014) - Landt, Hermine; Ward, Martin J.; Elvis, Martin; Karovska, Margarita
Abstract: Here we present observational evidence that the broad emission line region (BELR) of active galactic nuclei (AGN) generally has an outer boundary. This was already clear for sources with an obvious transition between the broad and narrow components of their emission lines. We show that the narrow component of the higher-order Paschen lines is absent in all sources, revealing a broad emission line profile with a broad, flat top. This indicates that the BELR is kinematically separate from the narrow emission line region. We use the virial theorem to estimate the BELR outer radius from the flat top width of the unblended profiles of the strongest Paschen lines, Paα and Paβ, and find that it scales with the ionizing continuum luminosity roughly as expected from photoionization theory. The value of the incident continuum photon flux resulting from this relationship corresponds to that required for dust sublimation. A flat-topped broad emission line profile is produced by both a spherical gas distribution in orbital motion and an accretion disc wind if the ratio between the BELR outer and inner radius is assumed to be less than ∼100–200. On the other hand, a pure Keplerian disc can be largely excluded, since for most orientations and radial extents of the disc the emission line profile is double-horned.